The sons of scripture : the Karaites in Poland and Lithuania in the twentieth century - Kizilov, Michail Borisovič 1974- (De Gruyter Open, 2015)
The Karaites, a non-Talmudic Turkic-speaking Jewish minority that had been living in Eastern Europe since the late Middle Ages, developed a unique ethnographic culture and religious tradition. The book offers the first comprehensive study of the dramatic history of the Polish-Lithuanian Karaite community in the twentieth century, especially the dejudaization of the community that saved the Karaites from horrors of the Holocaust.